2021
DOI: 10.2147/ppa.s311470
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Specific Health Literacy with a Digital Evidence-Based Patient Decision Aid for Hypertension: A Randomized Controlled Trial

Abstract: Introduction Health literacy is an important competency to make informed, shared decisions in line with patient’s preferences. On the other hand, lower health literacy is associated with poorer health outcomes. Evidence-based patient decision aids (EbPDA) are validated instruments to support informed medical decisions and empower patients for relevant involvement in their care. This study aimed to investigate the effect of a digital EbPDA for hypertension on health literacy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In our analysis, we observed few opportunities to adjust the presentation of the same information. Research has provided evidence that decision aids are effective in improving an individual's functional health literacy, which is essential for shared decisionmaking (38)(39)(40)(41)(42). However, differences in individual preferences, capabilities, knowledge, attitudes, and behaviors mean the optimal way to present CHI (e.g., textual, tabular, graphical, or audiovisual) varies between consumers (41,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we observed few opportunities to adjust the presentation of the same information. Research has provided evidence that decision aids are effective in improving an individual's functional health literacy, which is essential for shared decisionmaking (38)(39)(40)(41)(42). However, differences in individual preferences, capabilities, knowledge, attitudes, and behaviors mean the optimal way to present CHI (e.g., textual, tabular, graphical, or audiovisual) varies between consumers (41,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies already have reported that a limited understanding of medical knowledge, owing to a patient’s low level of health literacy, could act as a barrier for active participation in a treatment [ 8 10 , 12 , 13 ]. Therefore, several attempts for developing and offering decision aids for patients with low levels of health literacy by allowing them to be more informed and more involved in shared decision-making have been tried [ 24 26 ]. Those studies showed that such decision aids significantly encouraged patients’ active participation in decision-making and resulted in improvements to patients’ satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy will be observed as a predictor variable and will be determined using the 12-item version of the European Health Literacy Survey (HLS-Q12) 38. This instrument is derived from the widely used 47-item European Health Literacy Survey (HLS-EU-Q47),39 which has previously been used in patients with heart failure and hypertension 40 41. The HLS-Q12 was validated in a random sample of 900 Norwegian adults and is shown to have strong psychometric properties 42.…”
Section: Methods and Analysismentioning
confidence: 99%